Interspecies Variations in Bordetella Catecholamine Receptor Gene Regulation and Function - Brickman, Timothy J. (Infect Immun, 2015)
Bordetella bronchiseptica can use catecholamines to obtain iron from transferrin and lactoferrin via uptake pathways involving the BfrA, BfrD, and BfrE outer membrane receptor proteins, and although Bordetella pertussis has the bfrD and bfrE genes, the role of these genes in iron uptake has not been demonstrated. In this study, the bfrD and bfrE genes of B. pertussis were shown to be functional in B. bronchiseptica, but neither B. bronchiseptica bfrD nor bfrE imparted catecholamine utilization to B. pertussis. Gene fusion analyses found that expression of B. bronchiseptica bfrA was increased during iron starvation, as is common for iron receptor genes, but that expression of the bfrD and bfrE genes of both species was decreased during iron limitation. As shown previously for B. pertussis, bfrD expression in B. bronchiseptica was also dependent on the BvgAS virulence regulatory system; however, in contrast to the case in B. pertussis, the known modulators nicotinic acid and sulfate, which silence Bvg-activated genes, did not silence expression of bfrD in B. bronchiseptica. Further studies using a B. bronchiseptica bvgAS mutant expressing the B. pertussis bvgAS genes revealed that the interspecies differences in bfrD modulation are partly due to BvgAS differences. Mouse respiratory infection experiments determined that catecholamine utilization contributes to the in vivo fitness of B. bronchiseptica and B. pertussis. Additional evidence of the in vivo importance of the B. pertussis receptors was obtained from serologic studies demonstrating pertussis patient serum reactivity with the B. pertussis BfrD and BfrE proteins.